Investigating functional brain connectivity patterns associated with two hypnotic states - de Matos, Nuno M. P.; Staempfli, Philipp; Seifritz, Erich; Preller, Katrin; Bruegger, Mike (Frontiers in Human Neuroscience, 2023)
While there's been clinical success and growing research interest in hypnosis, neurobiological underpinnings induced by hypnosis remain unclear. In this fMRI study (which is part of a larger hypnosis project) with 50 hypnosis-experienced participants, we analyzed neural and physiological responses during two hypnosis states, comparing them to non-hypnotic control conditions and to each other. An unbiased whole-brain analysis (multi-voxel-pattern analysis, MVPA), pinpointed key neural hubs in parieto-occipital-temporal areas, cuneal/precuneal and occipital cortices, lingual gyri, and the occipital pole. Comparing directly both hypnotic states revealed depth-dependent connectivity changes, notably in left superior temporal/supramarginal gyri, cuneus, planum temporale, and lingual gyri. MVPA based seeds were implemented in a seed-to-voxel analysis unveiling region-specific increases and decreases in functional connectivity patterns. Physiologically, the respiration rate significantly slowed during hypnosis. Summarized, these findings foster fresh insights into hypnosis-induced functional connectivity changes and illuminate further knowledge related with the neurobiology of altered consciousness.This is a provisional file, not the final typeset article Sommer, 2021). According to the American Psychological Association (APA), a hypnotichypnosis is defined as "A state of consciousness involving focused attention and reduced peripheral awareness characterized by an enhanced capacity for response to suggestion". state is defined as a modified state of consciousness involving changes of the internal and external/environmental awareness (Elkins et al., 2015). There are different methods for hypnotizing a person. Spoken words with suggestible content are most commonly used for this so-calleda hypnosis induction (Zahedi and Sommer, 2021). A hypnotized person, depending of the hypnotic depth, might experience the following changes: feelings of deep mental and physical relaxation, mental absorption, diminishing of judging and monitoring, suspension of time and localization orientation, and sometimes the experience of automatic or extra-volitional own (motor) responses (